Scorpion venom increases acetylcholine release by prolonging the duration of somatic nerve action potentials. (15th July 2019) - O. Collaço, Rita de Cássia; Hyslop, Stephen; Dorce, Valquíria A.C.; Antunes, Edson; Rowan, Edward G.
Abstract: Scorpionism is frequently accompanied by a massive release of catecholamines and acetylcholine from peripheral nerves caused by neurotoxic peptides present in these venoms, which have high specificity and affinity for ion channels. Tityus bahiensis is the second most medically important scorpion species in Brazil but, despite this, its venom remains scarcely studied, especially with regard to its pharmacology on the peripheral (somatic and autonomic) nervous system. Here, we evaluated the activity of T. bahiensis venom on somatic neurotransmission using myographic (chick and mouse neuromuscular preparations), electrophysiological (MEPP, EPP, resting membrane potentials, perineural waveforms, compound action potentials) and calcium imaging (on DRG neurons and muscle fibres) techniques. Our results show that the major toxic effects of T. bahiensis venom on neuromuscular function are presynaptically driven by the increase in evoked and spontaneous neurotransmitter release. Low venom concentrations prolong the axonal action potential, leading to a longer depolarization of the nerve terminals that enhances neurotransmitter release and facilitates nerve-evoked muscle contraction. The venom also stimulates the spontaneous release of neurotransmitters, probably through partial neuronal depolarization that allows calcium influx. Higher venom concentrations block the generation of action potentials and resulting muscle twitches. These effects of the venom were reversed by low concentrations of TTX, indicating voltage-gated sodium channels as the primary target of the venom toxins. These results suggest that the major neuromuscular toxicity of T. bahiensis venom is probably mediated mainly by α- and β-toxins interacting with presynaptic TTX-sensitive ion channels on both axons and nerve terminals. Graphical abstract: Image 1 Highlights: Low concentrations of T. bahiensis venom enhanced spontaneous and evoked ACh release. At high concentrations, the venom blocked nerve conduction. Partial membrane depolarization could account for the enhanced spontaneous release. A conduction delay increased the quantal content by causing longer nerve depolarization. Tetrodotoxin-sensitive voltage-gated sodium channels are a major target of the venom.